Software engineering : principles and practice. - van Vliet, Hans, ....- (Chichester : Wiley, 2008)
Table of Contents 1 Introduction 2 Introduction to Software Engineering Management 3 The Software Life Cycle Revisited 4 Configuration Management 5 People Management and Team Organization 6 On Managing Software Quality 7 Cost Estimation 8 Project Planning and Control 9 Requirements Engineering 10 Modeling 11 Software Architecture 12 Software Design 13 Software Testing 14 Software Maintenance 15 Software Tools 16 User Interface Design 17 Software Reusability 18 Component-Based Software Engineering 19 Service Orientation 20 Global Software Development Bibliography Index